2007
DOI: 10.3141/2027-06
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Lane Width to Saturation Flow Rate on Urban and Suburban Signalized Intersection Approaches

Abstract: An understanding of the relationship between lane width and traffic operations is important in making decisions about urban and suburban arterials. Numerous geometric elements, including lane width, affect the saturation flow rate at an intersection on an urban or suburban arterial. Several studies have been conducted to evaluate the relationship between lane width and saturation flow rate at intersections. This relationship is investigated on urban and suburban signalized intersection approaches by using fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…In order to improve the accuracy of capacity estimation, adjustment factors become the focus of research. The common adjustment factors include lane width, vehicle composition, and various shared lanes [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Adjustment Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to improve the accuracy of capacity estimation, adjustment factors become the focus of research. The common adjustment factors include lane width, vehicle composition, and various shared lanes [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Adjustment Factorsmentioning
confidence: 99%
“…Based on the survey data, the relationship model of lane width and speed is developed. It is found that lane width is positively correlated with saturation flow rate [20][21][22]. Zegeer et al [20] studied the saturation flow rate at different scenarios in which the lane width of 2.6 to 4.7 m (8.5 to 15.5 ft).…”
Section: Adjustment Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the special road geometric conditions, mixed traffic composition, and very limited space, many transportation researchers and practitioners have proposed to shrink the width of existing approach lanes and save space for addition of extra lanes while it may bring negative impact on saturation flow rate, travel speed, and operational safety (Potts et al., ; Rosey et al., ; Isebrands et al., ; Wood et al., ). As an important element in geometric design of street, the lane width has long been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the lane width have been done for a long time, mostly investigating the effect of lane width on safety (2) and capacity (1,3), but fewer studies concern the effect on speed. As following, a comprehensive review of previous studies that dealt with the impact of lane width on speed will be presented from the aspects of highway/freeway.…”
Section: Literature Reviewmentioning
confidence: 99%